A long-life lithium–sulphur battery by integrating zinc–organic framework based separator. Issue 43 (18th October 2016) - Bai, Songyan; Zhu, Kai; Wu, Shichao; Wang, Yarong; Yi, Jin; Ishida, Masayoshi; Zhou, Haoshen
Abstract : Lithium–sulphur batteries have attracted increasing interest due to their high theoretical specific capacity, advantageous economy, and environmental friendliness. Abstract : Lithium–sulphur batteries have attracted increasing interest due to their high theoretical specific capacity, advantageous economy, and environmental friendliness. With migration of soluble lithium polysulfide (Li2 Sn, 4 < n ≤ 8) in mind, we prepared one novel Zn(ii ) metal–organic framework (MOF) based separator for lithium–sulphur batteries. It is able to play an efficient role as an ionic sieve for the soluble polysulfide ions. More importantly, the battery with Zn(ii )–MOF based separator exhibited much lower capacity decay of 0.041% per cycle at 1C over 1000 cycles.